ISOLATION OF AN ANTIFEEDANT TRITERPENOID FROM THE SEED OF Barringtonia asiatica - Emma J Pongoh; Rymond J Rumampuk; Ponis Tarigan; Anthony J Herlt; Lewis N Mander (Indonesian Journal of Chemistry, 2004)
An antifeedant triterpenoid saponin has been isolated from the seed of Barringtonia asiatica and its structure elucidated mainly by two dimensional NMR spectroscopy is identified as 3-O-{[β-D-galactopyranosyl(1→3)-β-D-glucopyranosyl (1→2)]-β-D-glucuronopyranosyloxy}-22-O-[2-(E)-methyl-2-butenyloyloxy]-15, 16,28-trihydroxy-(3β,15α,16α,22α)-olean-12-ene. This compound showed antifeedant activity towards Epilachna sp larvae